Explorers: pioneers who broke new bondaries - Platt, Richard; Chrisp, Peter (Dorling Kindersley London, 2001)
This is one of eight titles in this reference series covering a wide range of topics - from dinosaurs to explorers. This book on explorers includes photographs, facts and figures and relevant websites to explore